Evaluation of a Selective Prehospital Pediatric Spinal Protection Protocol. (2nd November 2019) - Ward, Caleb E.; Badolato, Gia Marissa; Breslin, Kristen; Brown, Kathleen; Simpson, Joelle N.
Abstract: Background: Recent studies demonstrate an association between spinal immobilization and neck pain, increased use of radiographs, and increased admission rates for pediatric trauma patients. There is an increasing trend toward spinal protection protocols that limit the use of backboards in trauma patients. However, many of these protocols do not address the youngest patients. Objectives: The objective was to analyze whether implementation of a selective prehospital pediatric spinal protection protocol was associated with a reduction in spinal imaging, hospital admission rates, and Emergency Department (ED) length of stay (LOS). Methods: We conducted a single center retrospective chart review to assess the effect of implementing a new selective pediatric spinal immobilization protocol in an EMS system. Patients transported to the same center from a neighboring EMS jurisdiction without a protocol change were analyzed for comparison. We extracted data for all pediatric patients with trauma-related discharge diagnoses transported by EMS to a pediatric trauma center for one year before and after the implementation of the protocol. Results: There were 878 eligible trauma patients transported under the new protocol, compared to 782 transported prior to implementation. We did not find a significant difference in the percentage of trauma patients who received spinal imaging pre- and post-protocol change (20% vs. 18%, OR 0.84 [95% CI 0.66, 1.07]), but did observe a significant reduction in the proportion of trauma patients who were admitted to the hospital (25% vs. 18%, OR 0.66 [95% CI 0.52, 0.83]). This reduced admission rate was not observed in the neighboring jurisdiction. Conclusions: Implementation of a selective spinal immobilization protocol was associated with reduced admission rates, but did not significantly reduce rates of plain radiographs.